Recyclable ferroferric oxide nanomaterial, preparation method and application

By synthesizing iron tetroxide nanoparticles and gold nanorod composite materials, the problem of low photothermal conversion efficiency of direct absorption solar collectors is solved, full-spectrum solar energy absorption and high-efficiency photothermal conversion are achieved, and the material is controlled to recover, avoiding heavy metal pollution.

CN118832177BActive Publication Date: 2025-04-29XIDIAN UNIV +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410803367.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-20
Publication Date
2025-04-29
Estimated Expiration
2044-06-20

AI Technical Summary

Technical Problem

In the prior art, the direct absorption solar heat collector has low photothermal conversion efficiency, the conventional fluid has low thermal conductivity, limited light absorption capacity, and nanofluids are prone to degradation at high temperatures, which limits its large-scale application.

Method used

By using ferric chloride and urea as raw materials, sodium citrate as stabilizer and sodium polyacrylate as dispersant, ferrous tetraoxide nanoparticles were synthesized by hydrothermal method, and the gold nanorods were modified with silica, and Fe3O4/Au@SiO2 composite material was formed by coupling the imidogen group to achieve full spectrum solar energy absorption.

Benefits of technology

The full-band spectral absorption performance of solar energy is improved, the solar energy collection and photothermal conversion performance is improved, and the production cost is reduced through the introduction of iron tetroxide, and the controllable recycling and reuse of nanoparticles is realized, and the secondary pollution of heavy metals is avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118832177B_ABST
    Figure CN118832177B_ABST
Patent Text Reader

Abstract

The present invention relates to a recyclable iron oxide-based nanomaterial, a preparation method and an application thereof. The preparation method includes: synthesizing highly monodisperse iron oxide nanoparticles by a hydrothermal method; preparing silica-modified gold nanorods Au@SiO2 by a seed growth method, wherein the silica-coated gold nanorods have different lengths; dispersing the silica-modified gold nanorod solutions with different lengths and 3-aminopropyltriethoxysilane to form a mixed solution, and adding the mixed solution to an aqueous solution of iron oxide nanoparticles for reaction to obtain an Fe3O4 / Au@SiO2 composite material. The iron oxide-based nanomaterial of the present invention not only has a wide range of solar absorption spectra, excellent photothermal conversion efficiency, and high magnetic saturation intensity, but also has a simple preparation process, low cost, and can be recycled and reused multiple times.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of energy materials, and in particular relates to a recyclable ferrosoferric oxide nanomaterial, a preparation method and an application thereof. Background Art

[0002] With the consumption of traditional fossil energy, problems such as resource shortage and ecological environment deterioration are becoming increasingly serious. Compared with fossil energy, renewable resources have shown great advantages and are expected to become the best substitute for fossil energy. Among them, solar energy is inexhaustible and does not pollute the environment, which has been highly valued by all countries. In recent years, solar energy has shown great potential in the fields of heat collection and heating, seawater desalination, refrigeration and power generation. It is expected that by 2100, solar energy is expected to reach 70% of global energy consumption. However, achieving more efficient use of solar energy still faces huge challenges.

[0003] Direct Absorption Solar Collector (DASC) is a very promising way to efficiently utilize solar energy. During the heat collection process, the thermal resistance of solar energy converted into working fluid heat energy is significantly reduced, the energy loss on the outer plate is very low, and most of the energy is absorbed by the fluid. In addition, the fluidity of the fluid makes the internal temperature uniform, which can effectively avoid potential overheating of the outer surface and minimize the radiation and convection heat loss of the solar collector, so as to achieve high energy conversion in the medium and high temperature areas. Using special working fluids to improve its photothermal conversion efficiency has become the focus of scholars. However, studies have found that conventional fluids such as water, oil, and ethylene glycol have low thermal conductivity and limited light absorption capacity, resulting in low photothermal conversion efficiency. In order to improve the photothermal conversion efficiency of DASC, researchers have replaced conventional fluids by adding inks and using black liquids. The results show that materials such as inks will degrade at high temperatures, which is not conducive to the large-scale application of DASC. In recent years, nanoparticles with a size of less than 100 nm have been dispersed in conventional fluids to obtain uniformly dispersed nanofluids, which have improved the heat transfer, optical properties and solar energy collection efficiency of DASC and have attracted great attention. However, nanofluids still face the following problems in practical application: (1) Some plasma nanoparticles are toxic and not suitable for water treatment or application to the human body, which may cause secondary pollution or cell death, limiting their large-scale application; (2) Nanoparticles have a narrow absorption range, limited ability to capture sunlight, and their photothermal performance needs to be further improved. Therefore, how to design nanoparticles that can recycle full-spectrum solar energy absorption is still a challenge for the efficient use and industrialization of solar energy. Summary of the invention

[0004] In order to solve the above problems existing in the prior art, the present invention provides a recyclable ferroferric oxide nanomaterial, a preparation method and an application. The technical problem to be solved by the present invention is achieved by the following technical solutions:

[0005] The embodiment of the present invention provides a method for preparing a ferroferric oxide nanomaterial capable of recycling full-spectrum solar energy absorption, comprising the steps of:

[0006] Ferrous oxide nanoparticles are synthesized by a hydrothermal method using ferric chloride and urea as raw materials, sodium citrate as a stabilizer, and sodium polyacrylate as a dispersant, wherein the surface of the ferrous oxide nanoparticles is modified with a carboxyl functional group;

[0007] sequentially adding a chloroauric acid solution and a sodium borohydride solution to a hexadecyltrimethylammonium bromide aqueous solution and stirring the mixture, and stopping stirring when the color of the reaction liquid changes to obtain a gold nanoparticle solution;

[0008] Adding different volumes of silver nitrate solution and chloroauric acid solution to an aqueous solution of hexadecyltrimethylammonium bromide and sodium oleate, adjusting the pH value of the solution with an acidic liquid, and then adding ascorbic acid and the gold nanoparticle solution to react and obtain gold nanorods with different lengths;

[0009] The aqueous solution of the gold nanorods is transferred to an aqueous solution of hexadecyltrimethylammonium bromide and the pH is adjusted to form an alkaline solution, and a mixed solution of tetraethyl silicate, 3-aminopropyltriethoxysilane and ethanol is added to the alkaline solution to react to obtain a gold nanorod solution modified with silicon dioxide, wherein amino functional groups are introduced on the surface of the silicon dioxide;

[0010] A solution of gold nanorods modified with silica of different lengths is dispersed with 3-aminopropyltriethoxysilane to form a mixed solution, and the mixed solution is added into an aqueous solution of the ferrosoferric oxide nanoparticles to react so that the carboxyl functional group is coupled with the amino functional group to form an amide group, thereby obtaining a Fe3O4 / Au@SiO2 composite material.

[0011] In one embodiment of the present invention, ferric chloride and urea are used as raw materials, sodium citrate is used as a stabilizer, and sodium polyacrylate is used as a dispersant, and a hydrothermal method is used to synthesize ferrosoferric oxide nanoparticles, comprising:

[0012] Dissolving the ferric chloride, the urea and the sodium citrate in deionized water, and adding the sodium polyacrylate under continuous stirring until dissolved; reacting the solution under the conditions of 2-20 MPa and 180-200° C., and sequentially subjecting the reaction product to magnetic separation, water washing and vacuum drying to obtain the ferrosoferric oxide nanoparticles with surface modified carboxyl functional groups;

[0013] Wherein, the mass ratio of the ferric chloride, the urea, the sodium citrate and the sodium polyacrylate is (1.0-1.4):(1.5-1.7):(3.4-3.6):(0.5-0.6).

[0014] In one embodiment of the present invention, a chloroauric acid solution and a sodium borohydride solution are sequentially added to a hexadecyltrimethylammonium bromide aqueous solution and stirred, and when the color of the reaction liquid changes, stirring is stopped to obtain a gold nanoparticle solution, comprising:

[0015] Prepare 0.18-0.22 mol / L hexadecyltrimethylammonium bromide aqueous solution;

[0016] Add 4.5-5.5 mL of the chloroauric acid solution with a concentration of 0.45-0.55 mmol / L to the hexadecyltrimethylammonium bromide aqueous solution, stir evenly, then add 500-700 μL of the sodium borohydride solution with a concentration of 0.008-0.011 mol / L, continue stirring, and stop stirring when the color of the reaction liquid changes from light yellow to brownish yellow to obtain the gold nanoparticle solution.

[0017] In one embodiment of the present invention, different volumes of silver nitrate solution and chloroauric acid solution are added to an aqueous solution of hexadecyltrimethylammonium bromide and sodium oleate, and ascorbic acid and the gold nanoparticle solution are added after the pH value of the solution is adjusted with an acidic liquid, and the reaction obtains gold nanorods with different lengths, including:

[0018] Adding hexadecyltrimethylammonium bromide and sodium oleate into deionized water to dissolve, the mass ratio of the hexadecyltrimethylammonium bromide to the sodium oleate being (7.0-7.4):(0.9-1);

[0019] The silver nitrate solution with a volume of 1.2-4.8 mL and a concentration of 3.8-4.2 mmol / L and the chloroauric acid solution with a volume of 190-210 mL and a concentration of 0.9-1.1 mmol / L are sequentially added to the dissolved solution and stirred evenly to form a reaction solution; the pH value of the reaction solution is adjusted with 1.6-1.8 mL of HCl; then 650-700 μL of ascorbic acid is added and stirred evenly, and then 620-660 μL of a gold nanoparticle solution is added as a gold seed to obtain a reaction mixture of gold nanorods after reaction; the reaction mixture is centrifuged to remove the hexadecyltrimethylammonium bromide, and the gold nanorods obtained by centrifugation are dispersed in deionized water for infiltration;

[0020] The volume of the silver nitrate solution is changed, and the above steps are repeated to obtain gold nanorods with different lengths.

[0021] In one embodiment of the present invention, the stirring rate after adding ascorbic acid is 1100-1300 rpm, and the stirring time is 25-35 s;

[0022] The reaction time after adding the gold nanoparticles is greater than or equal to 12 h;

[0023] The reaction mixture is centrifuged at a speed of 10500-11500 rpm.

[0024] In one embodiment of the present invention, the aqueous solution of the gold nanorods is transferred to an aqueous solution of hexadecyltrimethylammonium bromide and the pH is adjusted to form an alkaline solution, and a mixed solution of tetraethyl silicate, 3-aminopropyltriethoxysilane, and ethanol is added to the alkaline solution to react to obtain silicon dioxide-modified gold nanorods, comprising:

[0025] The aqueous solution of the gold nanorods is transferred to a 0.7-0.9 mmol / L hexadecyltrimethylammonium bromide aqueous solution, and the pH value of the solution is adjusted to 9.8-10 using 0.08-0.12 mol / L KOH. When the pH value of the solution is stable, a mixed solution of tetraethyl silicate, 3-aminopropyltriethoxysilane, and ethanol in a volume of 690-750 μL is added dropwise under stirring to obtain, after reaction, a gold nanorod modified with silica having amino functional groups introduced on the surface;

[0026] Wherein, the volume ratio of tetraethyl silicate, 3-aminopropyltriethoxysilane and ethanol is 1:0.05:4 vol%.

[0027] In one embodiment of the present invention, a solution of gold nanorods modified with silicon dioxide of different lengths is dispersed with 3-aminopropyltriethoxysilane to form a mixed solution, and the mixed solution is added to an aqueous solution of ferroferric oxide nanoparticles to react so that the carboxyl functional group is coupled with the amino functional group to obtain a Fe3O4 / Au@SiO2 composite material, comprising:

[0028] Mixing solutions of gold nanorods modified with silica of different lengths and centrifuging them to obtain a mixture; dispersing the mixture and 3-aminopropyltriethoxysilane in a mixed solution of ethanol and water and stirring to form the mixed solution; wherein the volume ratio of ethanol to water is 8:2;

[0029] The ferrosoferric oxide nanoparticles are dissolved in water to form an aqueous solution, and the mixed solution is added into the aqueous solution for stirring after ultrasonication to react, so that the carboxyl functional group is coupled with the amino functional group to obtain a Fe3O4 / Au@SiO2 composite material.

[0030] In one embodiment of the present invention, the silica-modified gold nanorod solution is centrifuged at a speed of 11000 rpm for a centrifugal time of 14-16 min.

[0031] Another embodiment of the present invention provides a recyclable full-spectrum solar energy absorbing ferroferric oxide nanomaterial, the chemical expression of which is Fe3O4 / Au@SiO2, comprising: silicon dioxide coated gold nanorods and ferroferric oxide nanoparticles, wherein the silicon dioxide coated gold nanorods have different lengths, and the ferroferric oxide nanoparticles are coupled to the silicon dioxide via an amide group;

[0032] The absorption spectrum of the ferroferric oxide nanomaterial is 400-1100nm;

[0033] The ferroferric oxide nanomaterial has magnetic properties.

[0034] Another embodiment of the present invention provides a use of a recyclable full-spectrum solar energy absorbing ferrosoferric oxide nanomaterial as a solar energy collection and heat conversion fluid in a direct absorption solar thermal collector.

[0035] Compared with the prior art, the present invention has the following beneficial effects:

[0036] In the ferroferric oxide-based nanomaterial prepared by the present invention, the surface of the gold nanorod is modified with silicon dioxide, the ferroferric oxide nanoparticles and the silicon dioxide are coupled by an amide group, the coupling of the Fe element and the noble metal Au nanorod is realized, and the plasmon coupling effect between Fe and the Au nanorods of different lengths is realized to realize a composite material with a broadband absorption spectrum, thereby solving the problem of the narrow absorption band of the Fe nanospheres or the Au nanorods, improving the full-band spectrum absorption performance of solar energy, and thus obtaining excellent solar energy collection and photothermal conversion performance; in addition, the introduction of ferroferric oxide not only serves as a photothermal agent, but also has excellent magnetic saturation intensity, and is more economical and practical than the noble metal Au, reducing the production cost, and can realize high-efficiency solar photothermal conversion efficiency and controllable recovery and reuse of nanoparticles without weakening the photothermal conversion performance of the nanostructure, avoiding secondary pollution of heavy metals, and realizing industrial application in the fields of solar thermal collection and heating. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 A schematic flow chart of a method for preparing a ferroferric oxide nanomaterial capable of recycling full-spectrum solar energy absorption provided by an embodiment of the present invention;

[0038] Figure 2 X-ray diffraction energy spectrum analysis diagram of Fe3O4 / Au@SiO2 composite material and Fe3O4 prepared in Example 1 of the present invention;

[0039] Figure 3 The scanning electron microscope image and transmission electron microscope image of the Fe3O4 / Au@SiO2 composite material prepared in Example 1 of the present invention;

[0040] Figure 4 The temperature rise and color change diagram of the Fe3O4 / Au@SiO2 composite material prepared in Example 1 of the present invention under magnetic field control;

[0041] Figure 5 Solar spectrum irradiation diagram of Fe3O4 / Au@SiO2 composite materials at different concentrations prepared in Example 1 of the present invention;

[0042] Figure 6 This is a comparison chart of the photothermal conversion efficiency of the Fe3O4 / Au@SiO2 composite material at different concentrations prepared in Example 1 of the present invention;

[0043] Figure 7 Absorption spectra of Fe3O4 / Au@SiO2 composite materials prepared in Examples 1, 2, 3, and 4 of the present invention;

[0044] Figure 8 The solar radiation temperature changes of the Fe3O4 / Au@SiO2 composite materials prepared in Examples 1, 2, 3, and 4 of the present invention. DETAILED DESCRIPTION

[0045] The present invention is further described in detail below with reference to specific embodiments, but the embodiments of the present invention are not limited thereto.

[0046] Embodiment 1

[0047] See also Figure 1 , Figure 1 A schematic flow chart of a method for preparing a ferroferric oxide nanomaterial that can absorb full-spectrum solar energy and can be recycled according to an embodiment of the present invention. The preparation method comprises the following steps:

[0048] S1. Ferrous oxide Fe3O4 nanoparticles were synthesized by hydrothermal method using ferric chloride and urea as raw materials, sodium citrate as stabilizer and sodium polyacrylate as dispersant.

[0049] Specifically, ferric chloride FeCl3, urea CO(NH2)2 and sodium citrate C6H5Na3O7 are dissolved in deionized water, and sodium polyacrylate PAAS is added under continuous stirring until dissolved; the solution is reacted under the conditions of 2-20Mpa and 180-200°C, and the reaction product is magnetically separated, washed with water and vacuum dried in sequence to obtain ferrosoferric oxide nanoparticles with carboxyl functional groups modified on the surface and highly dispersed, wherein the mass ratio of ferric chloride, urea, sodium citrate and sodium polyacrylate is (1.0-1.4):(1.5-1.7):(3.4-3.6):(0.5-0.6).

[0050] The reaction process of synthesizing ferroferric oxide nanoparticles by hydrothermal method is as follows:

[0051] In the first step, urea CO(NH2)2 will decompose at a high temperature of 180-200℃ to produce ammonia NH3, carbon dioxide CO2 and water H2O. The chemical equation is:

[0052]

[0053] In the second step, the generated ammonia gas NH3 reacts with water to form ammonia water NH3·H2O, and the ammonia water reacts with the ferric chloride FeCl3 in the solution to form ferric hydroxide Fe(OH)3 precipitation. The chemical equation is:

[0054] FeCl3+3NH3·H2O→Fe(OH)3↓+3NH4Cl.

[0055] In the third step, under high temperature and reducing atmosphere (CO2 and possibly H2 produced by the decomposition of urea), iron hydroxide Fe(OH)3 is reduced to ferroferric oxide Fe3O4, and the chemical equation is:

[0056] 4Fe(OH)3+CO2+H2→Fe3O4+4H2O+CO.

[0057] In this embodiment, sodium citrate C6H5Na3O7 is used as a stabilizer and sodium polyacrylate PAAS is used as a dispersant. These two substances are adsorbed on the surface of nanoparticles to prevent the particles from agglomerating, thereby maintaining the monodispersity of the particles and helping to form highly monodisperse ferroferric oxide nanoparticles. In addition, sodium polyacrylate PAAS will provide carboxyl groups to Fe3O4, forming Fe3O4 nanoparticles with surface modified carboxyl functional groups, so as to facilitate the next step of synthesis.

[0058] The product of this embodiment is dried under vacuum conditions because Fe3O4 has special magnetic properties, is an iron oxide, and has a crystal structure of ferrous ferrite. Vacuum drying can prevent Fe3O4 nanoparticles from being oxidized and hydrolyzed during the drying process, thereby destroying their magnetism and structure. On the other hand, since the nanoparticles have a large specific surface area and high surface energy, they are easy to adsorb water and oxygen, and vacuum drying can ensure the stability of the nanoparticles.

[0059] Exemplarily, 1.0-1.4g of ferric chloride FeCl3, 1.5-1.7g of urea CO(NH2)2 and 3.4-3.6g of sodium citrate C6H5Na3O7 are weighed and dissolved in about 150mL of deionized water, and then 0.5-0.6g of sodium polyacrylate PAAS is added under continuous stirring until it is completely dissolved. The dissolved solution is transferred to two 100mL polytetrafluoroethylene autoclaves (pressure is 2-20Mpa), placed in a 180-200℃ forced air drying oven for 4-4.5h to fully react. The reaction product is magnetically separated and washed 3 times with deionized water, and placed in a 60℃ vacuum oven to dry overnight to fully dry the Fe3O4 nanoparticles, and the dried Fe3O4 nanoparticles are ready for use.

[0060] In this embodiment, the use of a high-pressure reaction kettle and a blast drying oven can provide conditions for the hydrothermal reaction and keep the hydrothermal reaction going.

[0061] S2. Adding chloroauric acid solution and sodium borohydride solution to the aqueous solution of hexadecyltrimethylammonium bromide in sequence and stirring, and stopping stirring when the color of the reaction liquid changes to obtain a gold nanoparticle solution.

[0062] Specifically, first prepare a hexadecyltrimethylammonium bromide (CTAB) aqueous solution, then add a chloroauric acid (HAuCl4) solution to the hexadecyltrimethylammonium bromide (CTAB) aqueous solution, stir evenly, then add a sodium borohydride (3NaBH4) solution, continue stirring, and when the color of the reaction liquid changes from light yellow to brownish yellow, stop stirring to obtain a gold nanoparticle solution.

[0063] In this step, chloroauric acid reacts with sodium borohydride to generate gold nanoparticles, and the chemical equation is:

[0064] 2HAuCl4+2NaBH4+6H2O=2Au↓+2H3BO3+2NaCl+6HCl+5H2↑.

[0065] Exemplarily, a 0.18-0.22 mol / L aqueous solution of hexadecyltrimethylammonium bromide (CTAB) is placed in a 30°C water bath, and then a 4.5-5.5 mL aqueous solution of chloroauric acid (HAuCl4) with a concentration of 0.45-0.55 mmol / L is slowly added, and the reaction mixture is placed in a 28-32°C water bath for stirring (stirring speed is 1200 rpm), and after the solution is uniform, 500-700 μL of a newly prepared 0.008-0.011 mol / L aqueous solution of sodium borohydride (NaBH4) is quickly injected into the reaction solution, and stirring is continued for 2 min. It is observed that the color of the reaction liquid changes from light yellow to brownish yellow, and stirring is stopped and the mixture is placed in a water bath at a constant temperature of 28-32°C for 30 min for use.

[0066] In this embodiment, sodium borohydride has strong reducing properties and cannot be exposed to the air for a long time. Therefore, the newly prepared NaBH4 aqueous solution needs to be quickly added to the reaction solution; at the same time, a faster addition speed helps to reduce the occurrence of side reactions and improve the quality and purity of the product.

[0067] S3. Add different volumes of silver nitrate solution and chloroauric acid solution to an aqueous solution of hexadecyltrimethylammonium bromide and sodium oleate, adjust the pH value of the solution with an acidic liquid, then add ascorbic acid and gold nanoparticle solution to react and obtain gold nanorods with different lengths.

[0068] Specifically, cetyl trimethyl ammonium bromide CTAB and sodium oleate C 17 H 33 CO2Na is added into deionized water to dissolve, silver nitrate AgNO3 solution and chloroauric acid HAuCl4 solution are added into the dissolved solution in sequence and stirred evenly to form a reaction solution; the pH value of the reaction solution is adjusted with HCl; then ascorbic acid C6H8O4 is added and stirred evenly, and then a gold nanoparticle solution is added as a gold seed to obtain a reaction mixture of gold nanorods after reaction; the reaction mixture is centrifuged to remove hexadecyltrimethylammonium bromide, and the gold nanorods obtained by centrifugation are dispersed and infiltrated in deionized water.

[0069] Afterwards, the volume of the silver nitrate solution was changed and the above steps were repeated to obtain gold nanorods with different lengths.

[0070] The mass ratio of hexadecyltrimethylammonium bromide to sodium oleate is (7.0-7.4):(0.9-1). HCl can be concentrated hydrochloric acid with a concentration of 11-13 mol / L. The volume of the silver nitrate solution is 1.2-4.8 mL.

[0071] In this step, chloroauric acid reacts with ascorbic acid to generate gold nanorods, and silver nitrate reacts with ascorbic acid to regulate the longitudinal absorption peak of the gold nanorods. The chemical equation is:

[0072] HAuCl4+C6H8O6→Au+HCl+H2O+CO2↑;

[0073] AgNO3+C6H8O6→Ag+HNO3+H2O+CO2↑.

[0074] In this embodiment, the length of the gold nanorods is controlled by controlling AgNO3 and HCl.

[0075] Specifically, the longitudinal absorption peak of Au nanorods can be regulated by controlling the amount of AgNO3. When ascorbic acid is added, the Ag+ ions in the growth solution will be reduced to Ag atoms, and Ag will grow around the Au nanorods, and its deposition speed on the axial surface is much faster than the speed at both ends, thereby inhibiting the growth of the Au axial surface. When Ag is completely deposited on the axial surface of the nanorods, the Au nanorods also stop growing. Therefore, when the amount of AgNO3 added increases, the absorption peak will be red-shifted and the intensity will increase.

[0076] In addition, HCl is used to adjust the pH value of the reaction solution, and then ascorbic acid is added. The purpose of adding HCl is to change the pH of the solution, and the pH of the solution affects the ionization equilibrium of ascorbic acid. With the increase of hydrochloric acid, the ionization equilibrium of ascorbic acid will move toward the direction of generating ascorbic acid, so that the concentration of ascorbic acid molecules in the solution increases, thereby enhancing the reducing property and promoting the axial growth of the nano-gold rods. In other words, the longitudinal plasma absorption peak red-shifts with the increase of the amount of hydrochloric acid in the growth solution.

[0077] Furthermore, CTAB and sodium oleate act together as a dual surfactant system, and there is a synergistic effect between the two. This synergistic effect can better stabilize Au nanoparticles and promote their growth under specific conditions. Through the interaction with Au ions or the surface of Au nanoparticles, this interaction may change the charge state or interfacial tension on the surface of Au nanoparticles, affecting the growth rate and direction of Au nanorods.

[0078] Exemplarily, 7.0-7.4 g of hexadecyl trimethyl ammonium bromide (CTAB) and 0.9-1 g of sodium oleate (C) are mixed. 17 H 33CO2Na is mixed and added to 200mL of deionized water. In order to promote dissolution, the mixture is placed in a 70℃ water bath, stirred continuously for 30min, and then taken out and cooled to room temperature. Then 1.2-4.8mL of 3.8-4.2mmol / L silver nitrate AgNO3 aqueous solution is added, and the mixture is placed in a 30℃ water bath and stirred for 14-16min. 190-210mL of 1mmo / L HAuCl4 aqueous solution is added, and then stirred at 750-850rpm in the water bath for 90min. 1.6-1.8mL of HCl is added to the reaction solution to adjust the pH value and continue stirring for 15min. 650-700μL of ascorbic acid C6H8O4 is added, and the mixture is stirred vigorously at 1100-1300rpm for 25-35s. Finally, 620-660μL of the previously prepared gold seed is added to the growth solution, and the reaction solution is left to stand in a 30℃ water bath overnight. After that, the mixture was centrifuged for 15 min using a high-speed centrifuge (rotation speed of 10500-11500 rpm), the supernatant was poured out to remove the CTAB in the Au nanorods, and then the Au nanorods were redispersed in 50 mL of deionized water for soaking.

[0079] In this embodiment, vigorous stirring (rotation speed of 1100-1300 rpm) is required after adding ascorbic acid to ensure uniform mixing of the solution, promote the reduction reaction, maintain uniform concentration distribution in the solution, and avoid local concentration being too high or too low, thereby obtaining gold nanorods with controllable morphology and size.

[0080] The growth of gold rods is a relatively slow process that requires precise control. In this process, it is necessary to ensure that the various reactants are fully mixed in the solution. In this embodiment, the overnight addition of the gold seed is to allow the reactants in the solution to have enough time to fully contact, mix and react, thereby ensuring that the gold rods can grow in the expected manner.

[0081] It should be noted that the "overnight" involved in the present invention refers to a time greater than or equal to 12 hours, that is, the reaction time after adding gold nanoparticles is greater than or equal to 12 hours.

[0082] Hexadecyltrimethylammonium bromide (CTAB) is a surfactant used to control the growth and morphology of gold nanorods during the preparation of gold nanorods. However, excessive CTAB may have a negative impact on the performance and stability of gold nanorods. Therefore, centrifugation in a high-speed centrifuge at 10500-11500rpm can remove excess CTAB to ensure the purity and stability of gold nanorods.

[0083] S4. Transfer the aqueous solution of gold nanorods to an aqueous solution of hexadecyltrimethylammonium bromide and adjust the pH to form an alkaline solution, add a mixed solution of tetraethyl silicate, 3-aminopropyltriethoxysilane, and ethanol to the alkaline solution, and react to obtain a silica-modified gold nanorod solution, wherein amino functional groups are introduced onto the surface of the silica.

[0084] Specifically, the aqueous solution of gold nanorods is transferred to an aqueous solution of hexadecyltrimethylammonium bromide, and the pH value of the solution is adjusted to 9.8-10 using KOH. When the pH value of the solution is stable, a mixed solution of tetraethyl silicate, 3-aminopropyltriethoxysilane, and ethanol (TEOS / APTES / ethanol) is added dropwise under stirring. After the reaction, gold nanorods Au@SiO2 modified with silica having amino functional groups introduced on the surface are obtained.

[0085] In this step, tetraethyl silicate is hydrolyzed to form silicon dioxide, and the chemical formula is:

[0086] Si(OC2H5)4+4H2O=SiO2↓+4C2H5OH.

[0087] Furthermore, the generated silicon dioxide is coated on the surface of the gold nanorods.

[0088] In this embodiment, a TEOS / APTES / ethanol mixed solution is added, wherein 3-aminopropyltriethoxysilane is an organic silane, which can form a silica network together with tetraethyl silicate TEOS during hydrolysis and condensation, thereby introducing amino functional groups onto the surface of silica SiO2.

[0089] Exemplarily, the aqueous solution of gold nanorods is transferred to a 0.7-0.9 mmol / L CTAB (volume 200 mL) aqueous solution, and the pH is adjusted to 9.8-10 using 0.08-0.12 mol / L KOH, followed by equilibration in a 45°C water bath for 28-32 min to ensure that the pH and reaction temperature of the reaction solution are stable, and then 690-750 μL of a mixture of tetraethyl silicate TEOS / 3-aminopropyltriethoxysilane / ethanol (TEOS / APTES / ethanol, volume ratio of 1 / 0.05 / 4 vol%) is added dropwise three times (one-third each time) under gentle stirring, with an interval of 28-32 min each time, and finally the mixture is reacted in a 45°C water bath for 12 h to obtain silica-modified gold nanorods Au@SiO2 for use.

[0090] S5. Dispersing a solution of gold nanorods modified with silica of different lengths with 3-aminopropyltriethoxysilane to form a mixed solution, and adding the mixed solution into an aqueous solution of ferrosoferric oxide nanoparticles to react, so that the carboxyl functional group is coupled with the amino functional group to form an amide group, thereby obtaining a Fe3O4 / Au@SiO2 composite material.

[0091] Specifically, solutions of gold nanorods modified with silica of different lengths are mixed and centrifuged to obtain a mixture; the mixture and 3-aminopropyltriethoxysilane are dispersed in a mixed solution of ethanol and water and stirred to form a mixed solution; wherein the volume ratio of ethanol to water is 8:2;

[0092] The ferrosoferric oxide nanoparticles are dissolved in water to form an aqueous solution, and the mixed solution is added into the aqueous solution for stirring after ultrasonic treatment to react so that the carboxyl functional group is coupled with the amino functional group to obtain the Fe3O4 / Au@SiO2 composite material.

[0093] In this step, the amino functional groups on the surface of the silica-modified gold nanorods are combined with the carboxyl functional groups on the surface of the ferroferric oxide nanoparticles to form an amide group, thereby achieving the coupling of the silica-modified gold nanorods and the ferroferric oxide nanoparticles. The chemical equation is:

[0094] R-COOH+H2N-R'→R-CO-NH-R'+H2O.

[0095] Among them, the CONH bond is an amide group.

[0096] Exemplarily, a solution of Au@SiO2 modified with silica of different lengths is mixed to form a solution with a volume of 58-62 mL, centrifuged at 11000 rpm for 14-16 min, and then the mixture is dispersed in a mixture of 100 mL of ethanol and deionized water (volume ratio of ethanol: water = 8:2) with 1-2 mL of 3-aminopropyltriethoxysilane APTES and stirred for 4-5 h. 18-22 mg of Fe3O4 is weighed and ultrasonicated for 10 min to dissolve it in 45-55 mL of deionized water, and the above Au@SiO2 mixture is added, ultrasonicated for 10 min and stirred overnight (time is greater than or equal to 12 h) to ensure that Fe3O4 and Au@SiO2 are fully compounded, that is, Fe3O4 / Au@SiO2 is obtained, and Fe3O4 / Au@SiO2 is magnetically separated and dissolved in different amounts of deionized water to obtain Fe3O4 / Au@SiO2 of different concentrations.

[0097] In the ferroferric oxide-based nanomaterial prepared by the present invention, the surface of the gold nanorod is modified with silicon dioxide, the ferroferric oxide nanoparticles and the silicon dioxide are coupled by an amide group, the Fe element is coupled with the noble metal Au nanorod, and the composite material with a broadband absorption spectrum is realized through the plasmon coupling effect between Fe and the Au nanorods of different lengths, the problem of the narrow absorption band of the Fe nanospheres or the Au nanorods is solved, the full-band spectrum absorption performance of solar energy is improved, and thus excellent solar energy collection and photothermal conversion performance are obtained; in addition, the introduction of ferroferric oxide not only serves as a photothermal agent, but also has excellent magnetic saturation strength, and is more economical and practical than the noble metal Au, reducing the production cost, and can achieve high solar photothermal conversion efficiency and controllable recovery and reuse of nanoparticles without weakening the photothermal conversion performance of the nanostructure, thereby avoiding secondary pollution of heavy metals.

[0098] The preparation process of the ferroferric oxide-based nanomaterial Fe3O4 / Au@SiO2 that can recycle the full spectrum solar energy absorption in this embodiment is simple, low-cost, and recyclable and reuseable. It is a low-cost, high-efficiency new preparation method that can realize industrial applications in the fields of solar thermal heating.

[0099] Embodiment 2

[0100] On the basis of Example 1, this embodiment provides a recyclable ferroferric oxide-based nanomaterial that absorbs full-spectrum solar energy, and the chemical expression of the material is Fe3O4 / Au@SiO2. The material includes: silicon dioxide-coated gold nanorods and ferroferric oxide nanoparticles, wherein the silicon dioxide-coated gold nanorods have different lengths, and the ferroferric oxide nanoparticles are coupled to silicon dioxide through an amide group. The absorption spectrum of the ferroferric oxide-based nanomaterial is 400-1100nm, which can achieve full-spectrum solar energy absorption and efficient solar thermal conversion efficiency. The ferroferric oxide-based nanomaterial has magnetic properties, which can achieve controllable recycling and reuse of nanoparticles.

[0101] The ferroferric oxide-based nanomaterial of this embodiment has a wide range of solar energy absorption spectrum, excellent light-to-heat conversion efficiency, and high magnetic saturation intensity.

[0102] Embodiment 3

[0103] On the basis of Example 1 and Example 2, this embodiment illustrates the recyclable ferroferric oxide nanomaterial capable of absorbing full-spectrum solar energy and the preparation method thereof through the following examples.

[0104] Example 1

[0105] The specific preparation method of the recyclable full-spectrum solar energy absorbing FeO-based nanomaterial for solar thermal conversion in this example includes the following steps:

[0106] S1. Synthesize ferroferric oxide nanoparticles Fe3O4 by hydrothermal method.

[0107] Weigh 1.2g of ferric chloride FeCl3, 1.6g of urea CO(NH2)2 and 3.6g of sodium citrate C6H5Na3O7 and dissolve them in 160mL of deionized water, then add 0.6g of sodium polyacrylate PAAS under continuous stirring until completely dissolved. Transfer the solution to two 100mL polytetrafluoroethylene autoclaves and place them in a 200℃ forced air drying oven for 4h. Use deionized water to wash the product magnetically for 3 times, place it in a 60℃ vacuum oven and dry it overnight to obtain ferrosoferric oxide nanoparticles for later use.

[0108] S2. Prepare Au nanorods Au@SiO2 modified with silica SiO2 using the seed growth method.

[0109] S21. Prepare 0.2 mol / L hexadecyltrimethylammonium bromide (CTAB) aqueous solution and place it in a 30°C water bath. Then slowly add 5 mL of 0.5 mmol / L chloroauric acid (HAuCl4) aqueous solution. Place the reaction mixture in a water bath and stir (stirring speed is 1200 rpm). Subsequently, quickly inject 600 μL of freshly prepared 0.01 mol / L sodium borohydride (NaBH4) aqueous solution into the reaction mixture. Continue stirring for 2 min. Observe that the color of the reaction liquid changes from light yellow to brownish yellow. Stop stirring and place at a constant temperature of 30°C for 30 min to obtain a gold nanoparticle solution for use.

[0110] S22, 7.2g CTAB and 0.96g sodium oleate C 17 H 33CO2Na was mixed and added to 200mL of deionized water. In order to promote dissolution, the mixture was placed in a 70℃ water bath, stirred for 30min, and then taken out and cooled to room temperature. Then 1.2mL of 4mmol / L silver nitrate AgNO3 aqueous solution was added, placed in a 30℃ water bath and stirred for 15min, 200mL of 1mmol / L HAuCl4 aqueous solution was added, and then stirred at 800rpm for 90min. 1.7mL of HCl was added to the reaction solution to adjust the pH value and continued to stir for 15min. 670μL of ascorbic acid C6H8O4 was added and stirred vigorously for 30s. Finally, 640μL of the previously prepared gold nanoparticle solution was added to the growth solution as a gold seed, and the reaction solution was placed in a 30℃ water bath overnight and centrifuged for 15min by a high-speed centrifuge (11000rpm). After removing the CTAB in the Au nanorods, the Au nanorods were redispersed in 50mL of deionized water.

[0111] S23, the aqueous solution of Au nanorods was transferred to a 0.8mmol / L CTAB (200mL) aqueous solution, and the pH was adjusted to 10 with 0.1mol / L KOH. After balancing in a 45°C water bath for 30min, 720μL of a mixture of tetraethyl silicate TEOS / 3-aminopropyltriethoxysilane / ethanol (TEOS / APTES / ethanol, ratio of 1 / 0.05 / 4vol%) was added dropwise three times under gentle stirring, 240μL each time, with an interval of 30min each time, and the mixture was reacted in a 45°C water bath for 12h before use to obtain Au@SiO2, marked as Au 580nm (where 580nm represents the wavelength at the peak absorbance).

[0112] S3, according to the preparation method of step S2, the amount of 4mmol / L silver nitrate AgNO3 was changed to 2.4mL, 3mL, 3.6mL and 4.8mL respectively, to prepare Au nanorods modified with SiO2 of different lengths, which were marked as Au 630nm 、Au 701nm 、Au 802nm and Au 900nm .

[0113] S4. Preparation of recyclable ferroferric oxide-based nanocomposite material Fe3O4 / Au@SiO2.

[0114] Label 15 mL as Au 580nm Au@SiO2, 15mL is labeled as Au 630nm Au@SiO2, 15mL is labeled as Au 802nm Au@SiO2 and 15mL labeled Au 920nmAfter the mixture is evenly mixed with Au@SiO2, it is centrifuged at 1100rpm for 15min. Then, the mixture is dispersed with 2mL of APTES in a mixture of 100mL of ethanol and deionized water (ethanol: water volume ratio is 8:2) and stirred for 5h. Weigh 20mg of Fe3O4 nanoparticles and dissolve them in 50mL of deionized water by ultrasonication for 10 minutes. Add the above mixture, ultrasonicate for 10min and stir overnight to obtain Fe3O4 / Au@SiO2. After magnetic separation, Fe3O4 / Au@SiO2 is dissolved in different amounts of deionized water to obtain Fe3O4 / Au@SiO2 of different concentrations.

[0115] Furthermore, the Fe3O4 / Au@SiO2 composite material prepared in this example is used for solar thermal conversion. Specifically: the prepared Fe3O4 / Au@SiO2 nanofluid is placed in a beaker and placed on a bracket, and the upper port is sealed with an acrylic plate to prevent heat loss; the light intensity of a xenon lamp is used to simulate sunlight to irradiate the Fe3O4 / Au@SiO2 nanofluid, and the intensity of the xenon lamp is detected by a light intensity meter; a thermometer is placed at different positions to monitor the temperature of the nanofluid in real time to determine the temperature change; and a magnet is used to study the magnetically regulated thermal conversion performance.

[0116] See also Figure 2 , Figure 2 This is an X-ray diffraction energy spectrum analysis diagram of the Fe3O4 / Au@SiO2 composite material and Fe3O4 prepared in Example 1 of the present invention.

[0117] from Figure 2 From the X-ray diffraction energy spectrum analysis (XRD) diagram, it can be seen that the 2θ diffraction peaks at 30.1°, 35.4°, 43.1° and 62.5° correspond to the (2 2 0), (3 1 1), (4 0 0) and (4 4 0) crystal planes of Fe3O4, respectively. After interconnection with Au@SiO2, the 2θ diffraction peaks at 38.2°, 44.4°, 64.6° and 77.5° correspond to the (1 1 1), (2 0 0), (2 2 2) and (3 1 1) crystal planes of Au, respectively. The appearance of Au peaks in XRD indicates that the composite nanoparticles contain Au.

[0118] See also Figure 3 , Figure 3 Scanning electron microscope (SEM) and transmission electron microscope (TEM) images of the Fe3O4 / Au@SiO2 composite material prepared in Example 1 of the present invention.

[0119] from Figure 3 From the SEM in Figure (a), it can be seen that Au@SiO2 is densely covered around Fe3O4 and is stably connected to it. Figure 3Figure (b) is a TEM image of Fe3O4 / Au@SiO2 nanoparticles. The particle size of the nanoparticles was measured by Nano measure software. The larger particles are Fe3O4 nanoparticles with a diameter of about 200nm; the smaller ones are Au nanorods coated with SiO2, which are evenly covered on the surface with a layer thickness of about 1nm. The diameter of Au@SiO2 is about 20nm and the length is about 100nm. It can be seen from SEM and TEM that Fe3O4 and Au@SiO2 are tightly combined. Figure 3 Figure (c) is the EDS image of Fe3O4 / Au@SiO2 nanoparticles, and mapping analysis was performed on Fe, O, Si and Au. Through the analysis of Fe and O, spherical Fe3O4 can be observed, and the element distribution of Au and Si can distinguish the rod-shaped Au@SiO2. The uniform distribution of each element further indicates the successful connection between Fe3O4 and Au@SiO2. Figure 3 Figure (d) and Figure 3 Figure (e) in the middle is the high-resolution TEM images of Au and Fe3O4, respectively. The lattice spacing of the two planes is 0.201nm and 0.242nm, corresponding to the (2 0 0) crystal plane of Au and the (2 2 2) crystal plane of Fe3O4, respectively.

[0120] See also Figure 4 , Figure 4 This is a diagram of the temperature rise and color change of the Fe3O4 / Au@SiO2 composite material prepared in Example 1 of the present invention under magnetic field control.

[0121] Figure 4 (a) in the figure represents the temperature rise curve of Fe3O4 / Au@SiO2 nanofluid with and without magnetic field. The whole process is divided into three stages: In the first stage (0-600s), the temperature rise increases rapidly. Due to the influence of the magnetic field, the nanoparticles move rapidly along the direction of the magnetic field. More nanoparticles lead to stronger photothermal conversion performance, which makes the temperature near the magnetic field rise sharply. In the second stage (600-1200s), most nanoparticles are attracted to the cup wall. At this time, the photothermal conversion of the nanofluid is mainly contributed by a small number of nanoparticles and the base liquid. Due to convective heat transfer, the temperature rise tends to balance at this time, and the temperature difference between the part close to the magnetic field and the part away from the magnetic field remains constant. In the third stage (1200-1800s), almost all nanoparticles are attracted to the cup wall. Because the base liquid has a high transmittance to light and a weak capture ability, the rate of temperature rise decreases sharply. At this time, the temperature transfer between nanofluids is mainly based on flow heat transfer. The concentration of nanoparticles near the magnetic field is high and the temperature is high, and heat is transferred to the part away from the magnetic field. Therefore, the temperature difference between the two is reduced in this stage. Figure 4(b) shows the color change of Fe3O4 / Au@SiO2 solution after applying external magnetic field for 1min, 3min, 5min, 10min and 30min. It can be seen that the color gradually changes from turbid to clear. At 10min, the fluid color is basically clear, and at 30min, the color is basically the same as water, indicating that controlling the distribution of magnetic nanofluids by external magnetic field is a feasible method for collecting heavy metal magnetic nanoparticles.

[0122] See also Figure 5 , Figure 5 Solar spectral irradiation diagram of Fe3O4 / Au@SiO2 composite materials with different concentrations prepared in Example 1 of the present invention.

[0123] Calculate the solar absorption spectra of nanofluids with different concentrations, such as Figure 5 As shown. It can be seen that with the increase of nanofluid concentration, the curve of Fe3O4 / Au@SiO2 nanofluid gradually approaches the solar spectrum curve (orange curve in the figure). When the concentration of Fe3O4 / Au@SiO2 nanofluid is 0.0467vol%, the solar absorption energy is greatly improved, and the solar irradiance is close to 100%.

[0124] See also Figure 6 , Figure 6 This is a comparison chart of the photothermal conversion efficiency of Fe3O4 / Au@SiO2 composite materials with different concentrations prepared in Example 1 of the present invention.

[0125] from Figure 6 It can be seen that with the increase of concentration, the photothermal conversion efficiency gradually increases. Compared with Fe3O4@Au nanofluid, at 0.0067vol%, 0.0133vol% and 0.0267vol%, Fe3O4 / Au@SiO2 nanofluid increased by 13.96%, 5.11% and 3.91% respectively, indicating that the wide absorption spectrum can provide better photothermal conversion ability, and can achieve a high photothermal conversion efficiency at a lower concentration, which is conducive to reducing application costs.

[0126] Example 2

[0127] The specific preparation method of the recyclable full-spectrum solar energy absorbing FeO-based nanomaterial for solar thermal conversion in this example includes the following steps:

[0128] S1. Prepare ferrosoferric oxide nanoparticles Fe3O4 in the same manner as in Example 1.

[0129] S2. SiO2-modified Au nanorods Au@SiO2 were prepared in the same manner as in Example 1, except that the amounts of AgNO3 used in the preparation of Au@SiO2 were 3 mL and 3.6 mL, respectively, and the prepared Au@SiO2 were marked as Au 701nm and Au 802nm .

[0130] S3. Preparation of recyclable ferroferric oxide-based nanocomposite material Fe3O4 / Au@SiO2.

[0131] Mark 30mL as Au 701nm Au@SiO2 and 30mL labeled Au 802nm After the mixture is evenly mixed with Au@SiO2, it is centrifuged at 1100 rpm for 15 minutes. Then, the mixture is dispersed with 2 mL of APTES in a mixture of 100 mL of ethanol and deionized water (ethanol: water volume ratio is 8:2) and stirred for 5 hours. Weigh 20 mg of Fe3O4 and dissolve it in 50 mL of deionized water by ultrasonication for 10 minutes, add the above mixture, ultrasonicate for 10 minutes, and stir overnight to obtain Fe3O4 / Au@SiO2.

[0132] The Fe3O4 / Au@SiO2 composite material prepared in this example is used for solar thermal conversion. Specifically: the prepared Fe3O4 / Au@SiO2 nanofluid is placed in a beaker and placed on a bracket, and the upper port is sealed with an acrylic plate to prevent heat loss; the Fe3O4 / Au@SiO2 nanofluid is irradiated with xenon light to simulate sunlight, and the xenon light intensity is detected by a light intensity meter; thermometers are placed at different positions to monitor the temperature of the nanofluid in real time to determine temperature changes; and magnets are used to study the magnetically regulated thermal conversion performance.

[0133] Example 3

[0134] The specific preparation method of the recyclable full-spectrum solar energy absorbing FeO-based nanomaterial for solar thermal conversion in this example includes the following steps:

[0135] S1. Prepare ferrosoferric oxide nanoparticles Fe3O4 in the same manner as in Example 1.

[0136] S2. SiO2-modified Au nanorods Au@SiO2 were prepared in the same manner as in Example 1, except that the amounts of AgNO3 used in the preparation of Au@SiO2 were 3 mL and 3.6 mL, respectively, and the prepared Au@SiO2 were marked as Au 701nm and Au 802nm .

[0137] S3. Preparation of recyclable ferroferric oxide-based nanocomposite material Fe3O4 / Au@SiO2.

[0138] Label 20 mL as Au 701nm Au@SiO2 and 40mL labeled Au 802nm After the mixture is evenly mixed with Au@SiO2, it is centrifuged at 1100 rpm for 15 minutes. Then, the mixture is dispersed with 2 mL of APTES in a mixture of 100 mL of ethanol and deionized water (ethanol: water volume ratio is 8:2) and stirred for 5 hours. Weigh 20 mg of Fe3O4 and dissolve it in 50 mL of deionized water by ultrasonication for 10 minutes, add the above mixture, ultrasonicate for 10 minutes, and stir overnight to obtain Fe3O4 / Au@SiO2.

[0139] The Fe3O4 / Au@SiO2 composite material prepared in this example is used for solar thermal conversion. Specifically: the prepared Fe3O4 / Au@SiO2 nanofluid is placed in a beaker and placed on a bracket, and the upper port is sealed with an acrylic plate to prevent heat loss; the Fe3O4 / Au@SiO2 nanofluid is irradiated with xenon light to simulate sunlight, and the xenon light intensity is detected by a light intensity meter; thermometers are placed at different positions to monitor the temperature of the nanofluid in real time to determine temperature changes; and magnets are used to study the magnetically regulated thermal conversion performance.

[0140] Example 4

[0141] The specific preparation method of the recyclable full-spectrum solar energy absorbing FeO-based nanomaterial for solar thermal conversion in this example includes the following steps:

[0142] S1. Prepare ferrosoferric oxide nanoparticles Fe3O4 in the same manner as in Example 1.

[0143] S2. SiO2-modified Au nanorods Au@SiO2 were prepared in the same manner as in Example 1, except that the amounts of AgNO3 used in the preparation of Au@SiO2 were 3 mL and 3.6 mL, respectively, and the prepared Au@SiO2 were marked as Au 701nm and Au 802nm .

[0144] S3. Preparation of recyclable ferroferric oxide-based nanocomposite material Fe3O4 / Au@SiO2.

[0145] Label 40 mL as Au 701nm Au@SiO2 and 20mL labeled Au 802nmAfter the mixture is evenly mixed with Au@SiO2, it is centrifuged at 1100 rpm for 15 minutes. Then, the mixture is dispersed with 2 mL of APTES in a mixture of 100 mL of ethanol and deionized water (ethanol: water volume ratio is 8:2) and stirred for 5 hours. Weigh 20 mg of Fe3O4 and dissolve it in 50 mL of deionized water by ultrasonication for 10 minutes, add the above mixture, ultrasonicate for 10 minutes, and stir overnight to obtain Fe3O4 / Au@SiO2.

[0146] The Fe3O4 / Au@SiO2 composite material prepared in this example is used for solar thermal conversion. Specifically: the prepared Fe3O4 / Au@SiO2 nanofluid is placed in a beaker and placed on a bracket, and the upper port is sealed with an acrylic plate to prevent heat loss; the Fe3O4 / Au@SiO2 nanofluid is irradiated with xenon light to simulate sunlight, and the xenon light intensity is detected by a light intensity meter; thermometers are placed at different positions to monitor the temperature of the nanofluid in real time to determine temperature changes; and magnets are used to study the magnetically regulated thermal conversion performance.

[0147] See also Figure 7 , Figure 7 Absorption spectra of the Fe3O4 / Au@SiO2 composite materials prepared in Examples 1, 2, 3, and 4 of the present invention.

[0148] Figure 7 Au 701nm / Au 802nm When the ratio of addition is 2:1, the absorption peak blue shifts, while the absorption peaks in the visible and infrared regions decrease. In addition, when the volume ratio is 1:2, the absorption peak red shifts, and its absorption performance in the visible and infrared regions increases significantly. When the mixed volume ratio is the same (i.e. 1:1), the absorption peak trend becomes gentle, and the absorption range of solar energy becomes wider. When Au 580nm / Au 630nm / Au 802nm / Au 920nm Under equal proportion mixing, the absorption intensity is significantly enhanced in the visible light range, the absorption range is widened and the intensity is improved.

[0149] See also Figure 8 , Figure 8 The solar radiation temperature changes of the Fe3O4 / Au@SiO2 composite materials prepared in Examples 1, 2, 3, and 4 of the present invention.

[0150] From the photothermal results, it can be seen that the photothermal performance of the two mixed methods with the same proportion of addition is better. 580nm / Au 630nm / Au 802nm / Au 920nm The temperature rise is higher than Au 701nm / Au 802nmThe temperature rise under the hybrid mode shows that broadening the spectral absorption range can significantly change the photothermal conversion performance.

[0151] comprehensive Figure 4 , Figure 7 and Figure 8 You can get:

[0152] When the Fe3O4 / Au@SiO2 composite material prepared in Example 1 is used as a photothermal agent for solar energy collection and heat conversion, it has a stable absorbance in the range of 400-1100nm in the absorption spectrum, showing excellent wide-spectrum absorption. The temperature rise is 15°C after 1800s of irradiation with 1 sunlight, and the photothermal conversion efficiency is 81.79%, demonstrating efficient photothermal conversion capability. There are basically no nanoparticles in the solution 30 minutes after adsorption, and the solution has recyclability.

[0153] When the Fe3O4 / Au@SiO2 composite material in Example 2 is used as a photothermal agent for solar energy collection and heat conversion, it has good absorbance in the range of 400nm to 1100nm in the absorption spectrum, showing relatively excellent wide-spectrum absorption. The temperature rise after 1800s of irradiation with 1 sunlight is 12.9°C, and it has efficient photothermal conversion capability.

[0154] When the Fe3O4 / Au@SiO2 composite material in Example 3 is used as a photothermal agent for solar energy collection and heat conversion, it has good absorbance in the range of 400nm to 1100nm in the absorption spectrum, showing relatively excellent wide-spectrum absorption. The temperature rise after 1800s of irradiation with 1 sunlight is 12.9°C, and it has efficient photothermal conversion capability.

[0155] When the Fe3O4 / Au@SiO2 composite material in Example 4 is used as a photothermal agent for solar energy collection and heat conversion, it has good absorbance in the range of 400nm to 1100nm in the absorption spectrum, showing good wide-spectrum absorption. The temperature rise after 1800s of irradiation with 1 sunlight is 9.4°C, and it has photothermal conversion capability.

[0156] This embodiment selects Fe3O4 with excellent magnetic properties, environmental friendliness and lower cost to combine with Au nanorods of different lengths modified with SiO2, and utilizes the plasmon resonance effect of Fe3O4 and Au nanorods to improve the full-band spectrum absorption performance of solar energy, broaden the spectrum absorption range of solar energy, and thus obtain excellent solar energy collection and photothermal conversion performance. Fe3O4 has excellent magnetic properties, and its magnetic saturation intensity decreases slightly after coupling with Au nanorods, but the particles quickly gather in the strong magnetic field area under the control of the magnetic field, so that it can realize controllable recovery and active regulation of temperature distribution in solar thermal applications, which is not only environmentally friendly and lower in cost, but also makes the nanomaterials recyclable and repeatedly used, avoiding secondary pollution of heavy metals, and can realize industrial application.

[0157] Embodiment 4

[0158] On the basis of the above embodiments, this embodiment provides an application of a recyclable ferroferric oxide nanomaterial that absorbs full-spectrum solar energy as a solar energy collection and heat conversion fluid in a direct absorption solar collector.

[0159] The above contents are further detailed descriptions of the present invention in combination with specific preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, which should be regarded as falling within the protection scope of the present invention.

Claims

1. A method for preparing a ferroferric oxide nanomaterial capable of recycling full-spectrum solar energy absorption, characterized in that: Includes steps: Ferrous oxide nanoparticles are synthesized by a hydrothermal method using ferric chloride and urea as raw materials, sodium citrate as a stabilizer, and sodium polyacrylate as a dispersant, wherein the surface of the ferrous oxide nanoparticles is modified with a carboxyl functional group; sequentially adding a chloroauric acid solution and a sodium borohydride solution to a hexadecyltrimethylammonium bromide aqueous solution and stirring the mixture, and stopping stirring when the color of the reaction liquid changes to obtain a gold nanoparticle solution; Adding different volumes of silver nitrate solution and chloroauric acid solution to an aqueous solution of hexadecyltrimethylammonium bromide and sodium oleate, adjusting the pH value of the solution with an acidic liquid, and then adding ascorbic acid and the gold nanoparticle solution to react and obtain gold nanorods with different lengths; The aqueous solution of the gold nanorods is transferred to an aqueous solution of hexadecyltrimethylammonium bromide and the pH is adjusted to form an alkaline solution, and a mixed solution of tetraethyl silicate, 3-aminopropyltriethoxysilane and ethanol is added to the alkaline solution to react to obtain a gold nanorod solution modified with silicon dioxide, wherein amino functional groups are introduced on the surface of the silicon dioxide; A solution of gold nanorods modified with silica of different lengths is dispersed with 3-aminopropyltriethoxysilane to form a mixed solution, and the mixed solution is added into an aqueous solution of the ferrosoferric oxide nanoparticles to react so that the carboxyl functional group is coupled with the amino functional group to form an amide group, thereby obtaining a Fe3O4 / Au@SiO2 composite material.

2. The method for preparing the recyclable full-spectrum solar energy absorbing ferroferric oxide nanomaterial according to claim 1, characterized in that: Ferrous oxide nanoparticles are synthesized by hydrothermal method using ferric chloride and urea as raw materials, sodium citrate as stabilizer, sodium polyacrylate as dispersant, including: Dissolving the ferric chloride, the urea and the sodium citrate in deionized water, and adding the sodium polyacrylate under continuous stirring until dissolved; reacting the solution under the conditions of 2-20 Mpa and 180-200° C., and sequentially subjecting the reaction product to magnetic separation, water washing and vacuum drying to obtain the ferrosoferric oxide nanoparticles with surface modified carboxyl functional groups; Wherein, the mass ratio of the ferric chloride, the urea, the sodium citrate and the sodium polyacrylate is (1.0-1.4):(1.5-1.7):(3.4-3.6):(0.5-0.6).

3. The method for preparing the recyclable full-spectrum solar energy absorbing ferroferric oxide nanomaterial according to claim 2, characterized in that: Adding chloroauric acid solution and sodium borohydride solution to the aqueous solution of hexadecyltrimethylammonium bromide in sequence and stirring, and stopping stirring when the color of the reaction liquid changes, to obtain a gold nanoparticle solution, comprising: Prepare 0.18-0.22 mol / L hexadecyltrimethylammonium bromide aqueous solution; Add 4.5-5.5 mL of the chloroauric acid solution with a concentration of 0.45-0.55 mmol / L to the hexadecyltrimethylammonium bromide aqueous solution, stir evenly, then add 500-700 μL of the sodium borohydride solution with a concentration of 0.008-0.011 mol / L, continue stirring, and stop stirring when the color of the reaction liquid changes from light yellow to brownish yellow to obtain the gold nanoparticle solution.

4. The method for preparing the recyclable full-spectrum solar energy absorbing ferroferric oxide nanomaterial according to claim 1, characterized in that: Different volumes of silver nitrate solution and chloroauric acid solution are added to an aqueous solution of hexadecyltrimethylammonium bromide and sodium oleate, and ascorbic acid and the gold nanoparticle solution are added after the pH value of the solution is adjusted with an acidic liquid, and the gold nanorods with different lengths are obtained by reaction, including: Adding hexadecyltrimethylammonium bromide and sodium oleate into deionized water to dissolve, the mass ratio of the hexadecyltrimethylammonium bromide to the sodium oleate being (7.0-7.4):(0.9-1); The silver nitrate solution with a volume of 1.2 to 4.8 mL and a concentration of 3.8-4.2 mmol / L and the chloroauric acid solution with a volume of 190-210 mL and a concentration of 0.9-1.1 mmol / L are sequentially added to the dissolved solution and stirred evenly to form a reaction solution; the pH value of the reaction solution is adjusted with 1.6-1.8 mL of HCl; then 650-700 μL of ascorbic acid is added and stirred evenly, and then 620-660 μL of gold nanoparticle solution is added as a gold seed to obtain a reaction mixture of gold nanorods after reaction; the reaction mixture is centrifuged to remove the hexadecyltrimethylammonium bromide, and the gold nanorods obtained by centrifugation are dispersed in deionized water for infiltration; The volume of the silver nitrate solution is changed, and the above steps are repeated to obtain gold nanorods with different lengths.

5. The method for preparing the recyclable full-spectrum solar energy absorbing ferroferric oxide nanomaterial according to claim 4, characterized in that: The stirring rate after adding ascorbic acid was 1100-1300 rpm, and the stirring time was 25-35 s; The reaction time after adding the gold nanoparticles is greater than or equal to 12 h; The reaction mixture is centrifuged at a speed of 10500-11500 rpm.

6. The method for preparing the recyclable full-spectrum solar energy absorbing ferroferric oxide nanomaterial according to claim 1, characterized in that: The aqueous solution of the gold nanorods is transferred to an aqueous solution of hexadecyltrimethylammonium bromide and the pH is adjusted to form an alkaline solution, and a mixed solution of tetraethyl silicate, 3-aminopropyltriethoxysilane, and ethanol is added to the alkaline solution to react to obtain silicon dioxide-modified gold nanorods, comprising: The aqueous solution of the gold nanorods is transferred to a 0.7-0.9 mmol / L hexadecyltrimethylammonium bromide aqueous solution, and the pH value of the solution is adjusted to 9.8-10 using 0.08-0.12 mol / L KOH. When the pH value of the solution is stable, a mixed solution of tetraethyl silicate, 3-aminopropyltriethoxysilane, and ethanol is added dropwise in a volume of 690-750 μL under stirring to obtain a gold nanorod modified with silica having amino functional groups introduced on the surface after the reaction. Wherein, the volume ratio of tetraethyl silicate, 3-aminopropyltriethoxysilane and ethanol is 1:0.05:4 vol%.

7. The method for preparing the recyclable full-spectrum solar energy absorbing ferroferric oxide nanomaterial according to claim 1, characterized in that: A solution of gold nanorods modified with silicon dioxide of different lengths is dispersed with 3-aminopropyltriethoxysilane to form a mixed solution, and the mixed solution is added into an aqueous solution of ferroferric oxide nanoparticles to react so that the carboxyl functional group is coupled with the amino functional group to obtain a Fe3O4 / Au@SiO2 composite material, comprising: Mixing solutions of gold nanorods modified with silica of different lengths and centrifuging them to obtain a mixture; dispersing the mixture and 3-aminopropyltriethoxysilane in a mixed solution of ethanol and water and stirring to form the mixed solution; wherein the volume ratio of ethanol to water is 8:2; The ferrosoferric oxide nanoparticles are dissolved in water to form an aqueous solution, and the mixed solution is added into the aqueous solution for stirring after ultrasonication to react, so that the carboxyl functional group is coupled with the amino functional group to obtain a Fe3O4 / Au@SiO2 composite material.

8. The method for preparing the recyclable full-spectrum solar energy absorbing ferroferric oxide nanomaterial according to claim 7, characterized in that: The silica-modified gold nanorod solution is centrifuged at a speed of 11,000 rpm for 14-16 min.

9. A recyclable full-spectrum solar energy absorbing Fe3O4-based nanomaterial, characterized in that: Prepared by the preparation method according to any one of claims 1 to 8, the chemical expression of the ferroferric oxide-based nanomaterial is Fe3O4 / Au@SiO2, comprising: silicon dioxide-coated gold nanorods and ferroferric oxide nanoparticles, wherein the silicon dioxide-coated gold nanorods have different lengths, and the ferroferric oxide nanoparticles are coupled to the silicon dioxide via an amide group; The absorption spectrum of the ferroferric oxide nanomaterial is 400-1100 nm; The ferroferric oxide nanomaterial has magnetic properties.

10. A use of the recyclable full-spectrum solar absorption Fe3O4-based nanomaterial as claimed in claim 9 as a solar energy collection and heat conversion fluid in a direct absorption solar thermal collector.

Citation Information

Patent Citations

  • Preparation of ferriferrous oxide / gold / silicon dioxide nanoparticles of core-shell structure and drug release controlled through near-infrared light

    CN106511299A

  • Preparation method of ferroferric oxide / gold nanocomposite particles

    CN110211758A